Percursos, fragmentos e encontros: singularidades na docência - Simionato, Marli (2014)
This thesis approaches the journeys and meetings I have had in the teaching. Part of subjectivity understanding produced from multiple heterogeneous components, social experience and their singular routes. Today, more than ever, subjectivity is convened to singularize itself. It is in this perspective of singling that this research enplanes. The analysis was done by lines of affection, which were treated as potency to act, not as feelings themselves, but based on speeches and writings fragments, when I approached my perception of what produces me in teaching, rubbing with what I experience in the daily of Farroupilha Federal Institute - Panambi campus, and the readings I have done. The research is sustained in the theoretical assumptions of Gilles Deleuze, Félix Guattari and Baruch Espinosa, in particular in the concepts of arrangement, subjectivity, potency to act and meetings. The des/reterritorialization, lines of escape and the subjectivity out of the subject insert as folds in the research. In this cartographic confection, among authors and fragments, it was necessary to find a method that could sustain the intense anxieties that follow these moments of creation. Thus, the cartography allowed me to trace the intensive lines that gave rise to the concerns presented here. The care I had was to not fall into the representation of the subject who produces and who is produced on campus Panambi, but rather think of the arrangements that this space allows, because the individual only constitutes himself when broker. I highlight as one of the contributions of this study, the teaching when takes on new proportions, having the possibility to consider producing up teaching as a micropolitics found every step of the way, in a move that pulses, that intends and finds resonance in the creation, in the collective production, in the authorship, in the transversality of saying and listening, in the constitution of new senses to see in its vents, pipes that leaves the air circular with the outside, even at the risk of not always find good winds: this was my trip s script, this was my proposal.